2016
DOI: 10.4067/s0717-65382016000100004
|View full text |Cite
|
Sign up to set email alerts
|

Does the presence of livestock alter the trophic behaviour of sympatric populations of wild camelids Vicugna vicugna Molina 1782 and Lama guanicoe Müller 1976 (Artiodactyla: Camelidae)?: Evidence from Central Andes

Abstract: We described and compared the diets of two sympatric Andean camelids, during the humid season (austral summer) in a site of Northern Chile, in presence of domestic livestock. Results indicate that: 1) grasses and shrubs are the main component in the diet of both camelids, 2) shrubs were more consumed by V. vicugna; 3) V. vicugna and L. guanicoe used the same trophic resources but in different proportions; 4) in mountain environments, wetlands exploitation by wild camelids seems restricted by domestic cattle, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The contribution of grass species has been considered by various authors as the main component of the vicuña diet [7,8], representing around 70% of the total consumed species [4,5]. This coincides with what was obtained in this work but differs from results presented by Tirado et al [41], who report percentages of grasses of around 40% in vicuña diets in the Atacama Highland grassland. This could be attributed to important differences in the type of natural grasslands, since in our experimental conditions, the environment is more humid and the presence of shrub species was very low, not even being detected in the composition of the grasslands, as shown in Table 1.…”
Section: Diet's Botanical Compositionsupporting
confidence: 85%
See 1 more Smart Citation
“…The contribution of grass species has been considered by various authors as the main component of the vicuña diet [7,8], representing around 70% of the total consumed species [4,5]. This coincides with what was obtained in this work but differs from results presented by Tirado et al [41], who report percentages of grasses of around 40% in vicuña diets in the Atacama Highland grassland. This could be attributed to important differences in the type of natural grasslands, since in our experimental conditions, the environment is more humid and the presence of shrub species was very low, not even being detected in the composition of the grasslands, as shown in Table 1.…”
Section: Diet's Botanical Compositionsupporting
confidence: 85%
“…Borgnia et al [ 4 ] and Mosca and Puig [ 5 ], have also found a higher proportion of shrubs in the vicuña diet (10 to 17%), although under conditions that differ from the present study in terms of the availability and diversity of this group of plants. Even higher proportions are reported in a study by Tirado et al [ 41 ], who point out a contribution of shrub species of almost 34% in the summer diet of vicuñas in prairies of the Atacama highland ranges. Benítez et al [ 46 ] emphasize the impact of the shrub species of the steppes, on the quality of the vicuña diet, considering this group as an important resource in the last period of the wet–season, at which time the shrubs show low lignified twigs with high protein content.…”
Section: Discussionmentioning
confidence: 71%
“…Vicuna (V. vicugna), an endangered species protected by law, are found in the high plateau areas, between 3000 and 4600 m above sea level (Franklin 2011; Figure 2). Adult specimens of vicuna measure between 1.45 and 1.60 m, and usually weigh 35 to 65 kg (Cajal 1989;Aguilar et al 1995;Borgnia et al 2008;Cassini et al 2009;Franklin 2011;Tirado et al 2016).…”
Section: Vicuna and Its Environmentmentioning
confidence: 99%
“…The vicuna diet is based on grasses and shrubs (~80%), complemented by pseudograsses and herbs (Tirado et al 2016). These proportions are variable, however, and change following the sedentary and migratory tendencies of different populations according to seasonal and environmental restrictions (Franklin 1982;Contreras et al 2006).…”
Section: Vicuna and Its Environmentmentioning
confidence: 99%
See 1 more Smart Citation